Tourism collaborative governance: The views of tourism small and medium-sized enterprises in rural areas - Takalani Ramukumba (Interdisciplinary Journal of Management Sciences)
It is recognised that collaborative governance offers better solutions to problems than those fashioned exclusively by government agencies. Collaborative governance involves several relevant parties, particularly in the travel and tourism sector. The integrative processes of collaborative governance in the tourism industry provide a direct face-to-face alternative, leading to thorough and comprehensive strategic planning. Recent tourism governance research has explored the role of multiple actors in governing destinations but has not comprehensively investigated the role that tourism small and medium-sized enterprises play as important stakeholders at rural tourism destinations. Since tourism small and medium-sized enterprises are critical players in tourism collaborative governance, there is a need for an evaluation of the role they play in this context. This study explores the opinions of tourism small and medium-sized enterprises regarding collaborative governance at rural tourism destinations. The study adopted a qualitative research approach and employed a purposive sampling method, a non-probability sampling technique to select participants. Data were collected through semi-structured interviews. The results of the investigation indicate that tourism small and medium-sized enterprises recognise the need for their participation in tourism collaborative governance, the necessity of knowledgeable conveners, the importance of equal voices during stakeholder meetings, and mutual trust among stakeholders as essential components of effective collaborative governance. The study recommends active and equitable community participation, building mutual trust among stakeholders, and promoting effective collaboration between all parties involved in tourism collaborative governance.